5-methoxytryptophan ameliorates renal ischemia/reperfusion injury by alleviating endoplasmic reticulum stress-mediated apoptosis through the Nrf2/HO-1 pathway - Li, Shaona; Yang, Hongjuan; Zhang, Bing; Li, Lingyu; Li, Xiangkun (Frontiers in Pharmacology, 2025)
BackgroundRenal ischemia/reperfusion (I/R) injury is a prevalent clinical complication characterized by high incidence and mortality rates. The endogenous metabolite, 5-Methoxytryptophan (5-MTP), derived from tryptophan, possesses anti-inflammatory and antioxidant properties. However, its role in renal I/R injury remains unclear. In this study, we investigated whether 5-MTP could protect the kidney from I/R injury by ameliorating endoplasmic reticulum stress (ERS)-mediated apoptosis through the Nrf2/HO-1 pathway.Methods and resultsWe established models to examine renal I/R injury in C57BL/6J mice with bilateral renal pedicles clamped and HK-2 cells subjected to hypoxia/reoxygenation (H/R). The administration of 5-MTP improved renal tissue damage and kidney dysfunction impairment and reduced inflammation and oxidative stress. Moreover, 5-MTP attenuated ERS and ERS-mediated apoptosis, while upregulating Nrf2 and HO-1 expression. Additionally, Nrf2-deficient mice and cells were used to determine whether the Nrf2/HO-1 pathway was involved in the role of 5-MTP in alleviating ERS-mediated apoptosis. Nrf2 deficiency led to a partial reduction in the suppressive effects of 5-MTP on inflammation, oxidative stress, and ERS-mediated apoptosis.ConclusionOur findings suggest that 5-MTP alleviates renal I/R injury by inhibiting ERS-related apoptosis via the Nrf2/HO-1 pathway.